2021
DOI: 10.3389/fcimb.2021.734561
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into the Potential Value of Gut Microbial Signatures for Prediction of Gestational Anemia

Abstract: The gut microbiota alternations are associated with gestational anemia (GA); however, limited predictive value for the subsequent incidence of anemia in normal gestational women has been obtained. We sought to rigorously characterise gut dysbiosis in subjects with GA and explored the potential predictive value of novel microbial signatures for the risk of developing GA. A prospective cohort of subjects with GA (n = 156) and healthy control (n = 402), all of whom were free of GA in the second trimester, by 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although an increase in the relative abundance of Megamonas in ART‐treated HIV+ adults has been reported, 62 literature associating Megamonas with ID is scarce. A study in women with gestational anaemia reported gut microbial enrichment of Megamonas 63 . In HIV+ adults either on ART or ART naive, Megamonas was correlated significantly with interleukin‐6, a systemic inflammatory cytokine 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an increase in the relative abundance of Megamonas in ART‐treated HIV+ adults has been reported, 62 literature associating Megamonas with ID is scarce. A study in women with gestational anaemia reported gut microbial enrichment of Megamonas 63 . In HIV+ adults either on ART or ART naive, Megamonas was correlated significantly with interleukin‐6, a systemic inflammatory cytokine 64 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in women with gestational anaemia reported gut microbial enrichment of Megamonas . 63 In HIV+ adults either on ART or ART naive, Megamonas was correlated significantly with interleukin‐6, a systemic inflammatory cytokine. 64 In our study, HIV was significantly associated with increases in both CRP and AGP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The study was based on the Mother and Child Microbiome Cohort (MCMC) Study 16 , 18 . The study design is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence indicated that the community structure of the gut microbiota changes dramatically throughout pregnancy 12 , 13 , and perturbed gut microbiota during pregnancy was found to be associated with multiple commodities such as GDM 14 and inflammatory bowel disease 15 . Evidence also indicated the role of gut microbiota in predicting metabolic disorders 16 , 17 . However, whether the dynamic change of gut microbiota during gestation was associated with dyslipidemia and whether the gut microbiota structure can predict the risk of dyslipidemia is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Megamonas could act as a beneficial microbe. However, the overgrowth of Megamonas could be involved in the occurrence of gestational anemia ( Wei et al, 2021 ). Increased Megamonas abundance has been demonstrated to be associated with major depressive disorder ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%